2017
DOI: 10.1088/1361-6595/aa52a8
|View full text |Cite|
|
Sign up to set email alerts
|

Extended scaling and Paschen law for micro-sized radiofrequency plasma breakdown

Abstract: The single particle motion analysis and particle-in-cell merged with Monte Carlo collision (PIC/MCC) simulations are compared to explain substantial breakdown voltage reduction for helium microwave discharge above a critical frequency corresponding to the transition from the drift-dominant to the diffusion-dominant electron loss regime. The single particle analysis suggests that the transition frequency is proportional to the product ofp m and ( )where p is the neutral gas pressure, d is the gap distance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 32 publications
3
34
0
1
Order By: Relevance
“…Thus, the electron kinetic energy is examined rather than temperature. The PIC simulation results would be different from fluidor global simulations where the Maxwellian energy distribution is assumed and the kinetic effects are ignored.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the electron kinetic energy is examined rather than temperature. The PIC simulation results would be different from fluidor global simulations where the Maxwellian energy distribution is assumed and the kinetic effects are ignored.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the pulsed microwave DBD plasma sustained by the same driving voltage (Von=150 V) produces as much energetic electrons as in the bare electrode case. This is due to the characteristics of the α‐mode plasma which is rarely affected by γ . On the other hand, the DC pulse requires higher than 550 V to break down the gas and higher than 260 V to sustain the plasma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the onset of field emission in direct current microdischarges with gap sizes of the order of a few µm can lead to the breakdown at voltages far less than predicted by the standard scaling law. Deviations from the standard scaling law observed in microgaps can be described and explained by the quantum mechanical theory of field emission from metals [13][14][15][16][17][18]. * corresponding author; e-mail: marija@ipb.ac.rs…”
Section: Introductionmentioning
confidence: 99%
“…As is known, scaling laws are essential in understanding breakdown processes at different conditions and predicting discharge properties on different scales. [21][22][23]34,[49][50][51][52][53][54][55] The breakdown scaling law based on Townsend theory is usually investigated in cases with plane-parallel gaps when the electric field is uniform. 56,57 Previous studies indicate that Townsend theory is still valid in microdischarges unless the field emission plays a role.…”
mentioning
confidence: 99%